Analisis Faktor Kepuasan dan Niat Penggunaan Berkelanjutan Mobile Banking: Tinjauan User Experience, E-Service Quality, Perceived Security - Adristy Yumi Andini; Usep Suhud; Adnan Kasofi (Teewan Journal Solutions, 2026)
This study aims to examine the factors influencing users' continuance intention in using mobile banking, with a case study on the Wondr application by BNI. The main focus of this research lies in three variables: user experience, e-service quality, and perceived security, as well as their impact on customer satisfaction and continuance intention to use. The study employed a quantitative approach through the distribution of questionnaires. Data collection was conducted using a non-probability sampling method with a purposive sampling technique, involving 280 respondents who are active users of the Wondr application. The collected data were analyzed using Structural Equation Modeling (SEM) with the assistance of SPSS 27.0 and AMOS 29.0 software. The results show that user experience, e-service quality, and perceived security have a significant influence on customer satisfaction. Furthermore, user experience and customer satisfaction significantly affect continuance intention to use. However, e-service quality and perceived security do not have a significant impact on continuance intention. These findings provide practical contributions to the development of user retention strategies in mobile banking services.